Effect of diet, exercise and other contributing factors on menstruation - John, Agatha Mary; Saji, Angitha; Sunil, Krupa Ann; Thomas, Abel Abraham; Kumar, Abhilash B. (International Journal Of Community Medicine And Public Health, 2021)
Background: The poor knowledge and understanding of menstruation may lead to unsafe hygienic practice that in turn increases the risk of reproductive and genito-urinary tract infections and leads to overall poor quality of life. The food we consume have a complementary relationship with the pattern of menstrual cycle and so is the involvement of exercises. The study focused on understanding the relationship between effect of diet, exercise and other contributing factors on menstruation. Methods: The study was a prospective observational study done with a sample size of 650 subjects of 9 to 18 age group in whom menstruation already occurred who were recruited from five different schools in regions of Pathanamthitta and Alappuzha. Results: It was found that lack of exercise before and during menstruation has caused increased cramps and mood instability in girls. As well as skipping of breakfast and consumption of junk food was found to elevate pain, eventually affecting daily activities. Conclusions: The importance of counselling to all girls from the age of 9 was found to be necessary through the study and thereby adequate changes for a healthy future. Lack of exercise, unhealthy food habits and delayed identification of menstrual problems can have a negative impact on health.